2014
DOI: 10.1111/andr.270
|View full text |Cite
|
Sign up to set email alerts
|

Recent scenario of obesity and male fertility

Abstract: SUMMARYThe aim of this review was to provide current scenario linking obesity and male fertility. Obesity has been linked to male fertility because of lifestyle changes, internal hormonal environment alterations, and sperm genetic factors. A few studies assessing the impact of obesity on sperm genetic factor have been published, but they did not lead to a strong consensus. Our objective was to explore further the relationship between sperm genetic factor and obesity. There are emerging facts that obesity negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 135 publications
1
36
0
2
Order By: Relevance
“…As the basic semen parameters did not differ between MetS patients and controls, future investigations might include tests (i.e. mitochondrial membrane potential, proteome analysis) to study sperm integrity and fertilizing capacity at the molecular level (Kort et al, 2006;Leisegang et al, 2014;Shukla et al, 2014). In this study, we aimed to investigate the impact of low-grade systemic inflammation in patients with MetS on the seminal cytokine network and sperm parameters compared to agematched healthy controls, both groups without a history of infertility.…”
Section: Discussionmentioning
confidence: 99%
“…As the basic semen parameters did not differ between MetS patients and controls, future investigations might include tests (i.e. mitochondrial membrane potential, proteome analysis) to study sperm integrity and fertilizing capacity at the molecular level (Kort et al, 2006;Leisegang et al, 2014;Shukla et al, 2014). In this study, we aimed to investigate the impact of low-grade systemic inflammation in patients with MetS on the seminal cytokine network and sperm parameters compared to agematched healthy controls, both groups without a history of infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinic investigations show that abnormal semen parameters can attribute to obesity including decreased sperm concentration, decreased sperm motility and increased abnormal morphology (Shukla et al 2014, Guo et al 2017. Actually, obese men are more likely to exhibit a reduction in semen quality than men with a normal weight and responsible to high risk of infertility.…”
Section: Obesity Impairs Sperm Parametersmentioning
confidence: 99%
“…Recently, both clinical and experimental reveal the negative consequences of obesity on male reproductive function. According to the clinical investigation, men with overweight or obesity can decrease sperm quality including sperm concentration, sperm motility, acrosome reaction decline, increased sperm DNA damage and lower embryo implantation rates as well, comparing to those of normal BMI men (Jensen et al 2004, Dupont et al 2013, Samavat et al 2014, Shukla et al 2014, McPherson et al 2015, Soubry et al 2016. In consequence, obesity was associated with a more than 20% increased cases of subfertility and infertility (Cui et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While it has been reported that obese men are three times more likely to exhibit a reduction in sperm quality compared with men of normal weight (Sharma et al, 2013;Shulka et al, 2014), the true effect of obesity upon semen quality is a source of much debate. Numerous studies have shown that there is no relationship between increased BMI and one or more of the following semen parameters: sperm concentration, count, morphology, motility and ejaculate volume (Jensen et al, 2004;Fejes et al, 2006;Aggerholm et al, 2008;Hammoud et al, 2008;Paul et al, 2008;Nicopoulou et al, 2009;Chavarro et al, 2010;MacDonald et al, 2010;Martini et al, 2010;Povey et al, 2012;Hajshafi ha et al, 2013;Eisenberg et al, 2014;Pacey et al, 2014).…”
Section: Effects Upon Traditional Who Semen Parametersmentioning
confidence: 99%